Induction Motor Torque Measurement using Prony Brake System and Close-loop Speed Control - Hari Maghfiroh; Arthur Joshua Titus; Augustinus Sujono; Feri Adriyanto; Joko Slamet Saputro (International Journal of Robotics and Control Systems, 2022)
Three-phase induction motors are the main drivers of the industrial world because of their low price and good reliability. However, this type of motor does not have built-in speed control. These problems can be overcome by utilizing the Variable Frequency Drive (VFD) inverter. This research investigates the induction motor's characteristics in every load condition and combines a VFD inverter with an external speed controller based on Arduino. The motor is mounted on a Prony brake testbed frame to measure the motor's torque and mechanical power. The test results show the highest torque value obtained is 0.57 Nm, and the highest output power value is 0.042 kW. The motor cannot maintain the setpoint speed after loading in the open-loop control system. Meanwhile, the closed-loop control system has been successfully implemented, and the motor can return the speed to the setpoint value after loading, with an average settling time of 14.67 seconds.